2017
DOI: 10.2320/matertrans.m2016268
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Carbides in H13 Steel in Heat Treatment Process

Abstract: In the present work, the carbides in H13 steel were investigated with scanning electron microscope (SEM), energy dispersive spectrum (EDS), X-ray diffraction (XRD), and quantitative analysis method. The experimental results were compared with the calculation results by Thermo-calc software. The results show that the dendritic segregation exists generally in H13 ingots, primary M(C, N), M 6 (C, N) and a small amount of secondary carbides M 7 C 3 precipitate in the segregation area. The composition segregation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…2 and 3). In the literature, three different types of carbide with different shapes and sizes are mentioned [9,[15][16][17]. Type A (Figs.…”
Section: Microstructurementioning
confidence: 99%
See 1 more Smart Citation
“…2 and 3). In the literature, three different types of carbide with different shapes and sizes are mentioned [9,[15][16][17]. Type A (Figs.…”
Section: Microstructurementioning
confidence: 99%
“…Therefore, it can be said that carbide type and size are relevant to the number of tempering. In the literature, MC-type carbides in the microstructure of AISI H13 have been defined as primary carbides, while M 7 C 3 and M 23 C 6 type carbides have been defined as secondary carbides [7,17].…”
Section: Microstructurementioning
confidence: 99%
“…In fact, the amount of V-rich carbides is far more than that rich in Mo in the as-cast ingot. 7) The carbides type based on the component analysis can be characterized as follows: 8) MC V Fe Mo Cr C = 0 67 4 is main micro-alloying element distribution maps of as-cast H13 steel under EPMA. It can be clearly seen that micro-alloying elements (Cr, Mo, V) concentration is larger in grain boundary than inside of grains, which is the same with Fe, proving the existence of carbide of (Fe, M) x C y class 19) (where M represents Cr, V and Mo substituting for Fe).…”
Section: Characterization Of As-cast Microstructurementioning
confidence: 99%
“…A higher Mo content in Dievar leads to a higher hardenability and a greater tempering resistance with a uniform distribution of Mo-rich M 2 C carbides in the ferritic matrix responsible for the secondary hardening effect [2,10,11]. The decomposition from metastable needle-like M 2 C carbides to M 6 C carbides with a narrow thermodynamic stability region has also been reported to occur at tempering temperatures above 600°C [8]. Mass fraction of Mo-rich M 6 C carbides is lower than that of Cr-rich M 7 C 3 and M 23 C 6 carbides due to its narrow thermodynamic stability region [12].…”
Section: Introductionmentioning
confidence: 99%
“…The formation of M 7 C 3 and M 23 C 6 takes place either via the in situ transformation from alloyed cementite as Cr can take the place of iron atoms in cementite if there is sufficient soluble Cr in solid solution or by the separate nucleation in the ferritic matrix and along grain/subgrain boundaries [16,17]. Furthermore, there are two morphologies of V-rich MC/M 8 C 7 carbides present on tempering at high temperatures for a longer time: larger and circular ones (primary carbides) and a fine dispersion of nano-sized ones derived from the transformation from other less thermal stable alloy carbides [5,8,9]. It has been shown that the uniform and fine dispersion of Mo-rich M 2 C and V-rich MC/ M 8 C 7 carbides in the ferritic matrix not only contributes to the secondary hardening but also confines the coarsening of martensitic laths, which further contributes to a higher tempering resistance in terms of maintaining high strength and excellent toughness for this grade of steel [18,19].…”
Section: Introductionmentioning
confidence: 99%